Computed Tomography-Based Analysis of Implant Positioning after Total Knee Arthroplasty: A Randomized Controlled Trial Comparing Conventional and Robotic Arm-Assisted Procedures - Horteur, Clément; Gaulin, Benoit; Pascal, Pierre; Leroy, Corentin; Giai, Joris; Murgier, Jérôme; Barth, Johannes; Pailhé, Régis (The Journal of Knee Surgery, 2025)
The aim of this study was to evaluate the deviation from the surgical plan of femoral and tibial components positioning after robotic total knee arthroplasty (R-TKA) compared with conventional TKA (C-TKA) based on postoperative three-dimensional computed tomography (3D-CT). This prospective randomized trial included 60 patients: 29 in the C-TKA group and 31 in the R-TKA one. Early postoperative 3D-CT-based analysis of implants positioning was performed. Measurements were performed twice by two observers, showing good to excellent intra- and interobserver reproducibility (interclass coefficient ranging from 0.71 to 0.96). Absolute deviations from the surgical plan (mechanical alignment in the C-TKA group and personalized alignment in the R-TKA group) were compared between groups. Primary endpoint was coronal lower limb frontal alignment: hip–knee–ankle (HKA) angle. Secondary endpoints were frontal, sagittal, and rotational positioning of both tibial and femoral components. Planned frontal lower limb alignment was similarly achieved in both group: HKA angle mean difference was 2.28 ± 1.81 degrees in the C-TKA group and 1.84 ± 1.46 degrees in the R-TKA group (p = 0.379). Deviations from the surgical plan were lower in the R-TKA group compared with the C-TKA group for all parameters, except tibial rotation (9.02 ± 4.51 vs. 7.42 ± 3.96 degrees, respectively). These differences turned out to be statistically significant only for sagittal alignment of both femoral (1.71 ± 1.34 vs. 3.61 ± 2.05 degrees, p < 0.001) and tibial (3.78 ± 1.15 vs. 4.94 ± 1.99 degrees, p = 0.018) components. Accuracy in achieving planned coronal lower limb alignment is not higher using R-TKA compared with C-TKA. Regarding component positioning, R-TKA appears superior in the sagittal plane while no significant differences were identified in terms of frontal alignment and rotation.Level of Evidence I.
Keywords: robotic; total knee arthroplasty; computed tomography